2016
DOI: 10.1103/physrevlett.116.154501
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Behavior for Ionic Transport and its Fluctuations in Individual Carbon Nanotubes

Abstract: In this Letter, we perform an experimental study of ionic transport and current fluctuations inside individual carbon nanotubes (CNTs). The conductance exhibits a power law behavior at low salinity, with an exponent close to 1/3 versus the salt concentration in this regime. This behavior is rationalized in terms of a salinity dependent surface charge, which is accounted for on the basis of a model for hydroxide adsorption at the (hydrophobic) carbon surface. This is in contrast to boron nitride nanotubes which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
320
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(343 citation statements)
references
References 27 publications
18
320
5
Order By: Relevance
“…DOI: 10.1103/PhysRevE.94.050601 The ionic conductance, G, of carbon nanotubes (CNTs) is of relevance for applications in membrane technology for water desalination, energy harvesting, and energy conversion [1][2][3][4][5][6]. Secchi et al [7,8] recently reported the first experimental results for G of single carbon nanotubes of different radii and lengths, in a large salt concentration range (1-1000 mM) and at several values of pH. The observed dependence of G on pH, and the absence of a plateau in G at low salinity, were taken as evidence that CNTs acquire a surface charge by reversible adsorption of hydroxyl ions from water.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…DOI: 10.1103/PhysRevE.94.050601 The ionic conductance, G, of carbon nanotubes (CNTs) is of relevance for applications in membrane technology for water desalination, energy harvesting, and energy conversion [1][2][3][4][5][6]. Secchi et al [7,8] recently reported the first experimental results for G of single carbon nanotubes of different radii and lengths, in a large salt concentration range (1-1000 mM) and at several values of pH. The observed dependence of G on pH, and the absence of a plateau in G at low salinity, were taken as evidence that CNTs acquire a surface charge by reversible adsorption of hydroxyl ions from water.…”
mentioning
confidence: 99%
“…The observed dependence of G on pH, and the absence of a plateau in G at low salinity, were taken as evidence that CNTs acquire a surface charge by reversible adsorption of hydroxyl ions from water. A theoretical analysis led to a 1/3 power-law scaling of G with salt concentration, which is supported by the data.In the present work, to describe the same data of Secchi et al [7,8], we use the general classical dilute solution theory for long and thin capillary pores, combining the extended Nernst-Planck equation with the Stokes equation for fluid flow and the Poisson-Boltzmann (PB) equation for the structure of the electrical double layer (EDL), evaluated in radial direction. This model was developed by Osterle and co-workers [9,10] and is known as the capillary pore model, or space charge (SC) theory.…”
mentioning
confidence: 99%
See 3 more Smart Citations